Enhancing Paediatric and Strabismus Ophthalmology Departments in Spain Through the Inclusion of Orthoptists: Insights from a Nationwide Survey - Ana María Cruz Lasso (British and Irish Orthoptic Journal)
Background and objectives: The absence of the orthoptic profession in Spain contrasts with its value and recognition in other countries. This study aimed to gauge Spanish ophthalmologists’ interest in including and promoting orthoptists in paediatric and strabismus departments. Secondary objectives included assessing interest in requesting orthoptists, involvement in their training, and aligning their competencies with European standards. Methodology: Participants were recruited via WhatsApp and flyers during the 30th SEEOP Congress in May 2023 and invited to review a report on orthoptists’ significance followed by completing a 12-question online survey. Profile questions were asked via multiple-choice options. Opinions on integrating orthoptists to enhance care quality, training involvement, and alignment with European standards were rated using a Likert scale. Open-ended questions captured themes, and comments. Results: Forty-two paediatric and strabismologists in Spain participated, mostly hospital-employed with advanced degrees, 90% supported integrating orthoptists into their teams, with 83% interested in having them in their workplace. Nearly 90% believed that collaboration between ophthalmologists and orthoptists would improve care quality and reduce waiting lists, and 83% supported promoting this within national medical organisations. Additionally, 90% advocated level 4 advanced European-standard training for orthoptists and 25% were neutral about participating in training orthoptists. Participants emphasised the importance of qualified orthoptists for treating eye movement abnormalities, distinguishing them from other eye healthcare professionals and advocating for collaboration rather than replacement. Conclusions: This initial survey of paediatric ophthalmologists and strabismologists in Spain highlights support for orthoptists as allied health professionals, though garnering support for their training could be challenging. These conclusions should be considered in light of methodological, sample size, and resource limitations. The survey serves as a pilot for the future, suggesting improvements to explore the feasibility of introducing orthoptists in Spain.